Personal Information Management - Teevan, Jaime (Seattle: University of Washington Press, 2007)
In an ideal world, everyone would always have the right information, in the right form, with the right context, right when they needed it. Unfortunately, we do not live in an ideal world. This book looks at how people in the real world currently manage to store and process the massive amounts of information that overload their senses and their systems, and discusses how tools can help bring these real information interactions closer to the ideal. Personal information management (PIM) is the study and practice of the activities people perform to acquire, organize, maintain, and retrieve information for everyday use. PIM is a growing area of interest as we all strive for better use of our limited personal resources of time, money, and energy, as well as greater workplace efficiency and productivity. Personal information is currently fragmented across electronic documents, email messages, paper documents, digital photographs, music, videos, instant messages, and so on. Each form of information is organized and used to complete different tasks and to fulfill disparate roles and responsibilities in an individual’s life. Existing PIM tools are partly responsible for this fragmentation. They can also be part of the solution that brings information together again. A major contribution of this book is its integrative treatment of PIM-related research. The book grows out of a workshop on PIM sponsored by the National Science Foundation, held in Seattle, Washington, in 2006. Scholars from major universities and researchers from companies such as Microsoft Research, Google, and IBM offer approaches to conceptual problems of information management. In doing so, they provide a framework for thinking about PIM as an area for future research and innovation.